2023
DOI: 10.3390/polym15071606
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Accelerated Aging on the Fiber-Matrix Adhesion of Regenerated Cellulose Fiber-Reinforced Bio-Polyamide

Abstract: With regard to the sustainability and biological origin of plastic components, regenerated cellulose fiber (RCF)-reinforced polymers are expected to replace other composites in the future. For use under severe conditions, for example, as a housing in the engine compartment, the resistance of the composites and the impact on the fiber and fiber-matrix adhesion must be investigated. Composites of bio-polyamide with a reinforcement of 20 wt.% RCF were compounded using a twin-screw extruder. The test specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…[ 31 ] Similar behavior was seen for bio‐Polyamide/regenerated cellulose fiber composites due to swelling and shrinkage of the fibers. [ 50 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Similar behavior was seen for bio‐Polyamide/regenerated cellulose fiber composites due to swelling and shrinkage of the fibers. [ 50 ]…”
Section: Discussionmentioning
confidence: 99%
“…This proves that the fiber volume fraction affects the evaluation results of IFSS, and previous experiments have had difficulty controlling the fiber volume fraction. Falkenreck et al [21], Barrera-Fajardo et al [22], and Liu et al [23] reported the effects of a natural fiber surface treatment on the mechanical properties of composites. These mechanical properties include tensile strength, bending strength, and surface friction, and so on.…”
Section: Introductionmentioning
confidence: 99%